Answer: (-5, -8)
======================================================
Step-by-step explanation:
We get this point by doing two things.
- Subtract 2 from the x coordinate, due to the x-2
- Subtract 7 from the y coordinate, because of the y-7
If we started with x = -3, then x-2 = -3-2 = -5. Also, if we had y = -1 then y-7 = -1-7 = -8
So that's how we end up with Z(-3,-1) moving to Z ' (-5, -8)
You could also show your work like this
![(x,y) \to (x-2, y-7)\\\\(-3,-1) \to (-3-2, -1-7)\\\\(-3,-1) \to (-5, -8)\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/4fjfsfoaluzz57f7ogh6o0bwfxdfprg8u3.png)